PENGARUH PENERAPAN MODEL TEAM ASSISTED INDIVIDUALIZATION DALAM PEMBELAJARAN TEMATIK - Hardiningrum, Esti Dwi; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe main issue on this article discusses how the application of the team assisted model caninfluence students in thematic learning. In order to provide answers to these problem, this articleanalyzes Class V Student Learning Outcomes set at SDN 03 Sungai Raya as a research location.The experimental method in the form of a quasy experimental study with a non-equivalent controlgroup design was applied as a research method. The population in this research consist of 79students. Sampling technique used is sampling purposive obtained from class VB samples as theexperimental class and VC as the control class. Based of research analisys it is obtained that tcount(2,024) > ttable (2,020) which mean Ha is accepted. Based on the calculation of Effect Size obtained0,61 which is categorized as average criteria. This article concludes that there is an effect by usingteam assisted individualization models on thematics learning Class V SDN 03 Sungai Raya.Keywords: Influence, Team Assisted Individualization, Learning Outcomes